A review of the genus Agalope Walker (Lepidoptera, Zygaenidae, Chalcosiinae) with taxonomic notes and descriptions of three new genera and three new species - Huang, Si-Yao; Horie, Kiyoshi; Fan, Xiao-Ling; Wang, Min; Espeland, Marianne (Zootaxa, 2023)
A preliminary review of the genus Agalope Walker, 1854 is presented. Two new genera are established for four species-groups: Rotundagalope S.-Y. Huang & Horie, gen. n. (type species Agalope immaculata Leech, 1898, for the immaculata species-group), Paragalope S.-Y. Huang & Horie, gen. n. (type species Chelura pica Wileman, 1910, for the pica, glacialis and dejeani species-groups). An additional new genus, Agacysma S.-Y. Huang & Horie, gen. n., related to Agalope and Elcysma, is erected for the new species Agacysma sinica S.-Y. Huang & Horie sp. n. (mainland China: Chongqing, Hubei & Shaanxi). Two new species of the genus Agalope are described: A. geoffi S.-Y. Huang & Horie sp. n. (mainland China: SE. Xizang) and A. liuzihaoi S.-Y. Huang & Horie sp. n. (mainland China: SE. Xizang), forming a species-group of their own which is clearly different from congeners in their male genitalia. The taxonomic issues between Paragalope haoi (S.-Y. Huang, 2022) comb. n. and P. bieti (Oberthür, 1886) comb. n. are discussed. Moreover, following the erection of Paragalope, the homonymy of Agalope glacialis Butler, 1881 and A. glacialis (Moore, 1872) ends; hence the replacement name of the former, A. butleri Owada & Horie, 2000 syn. n., is unnecessary and hence synonymized. The following new combinations are given: Rotundagalope immaculata (Leech, 1898) comb. nov., Paragalope ardjuna (Roepke, 1936) comb. nov., P. aurelia (Oberthür, 1923) comb. nov., P. basiflava (Moore, 1879b) comb. nov., P. bieti (Oberthür, 1886) comb. nov., P. chayuensis (S.-Y. Huang & Pan, 2022) comb. nov., P. haoi (S.-Y. Huang, 2022) comb. nov., P. owadai (S.-Y. Huang, 2022) comb. nov., P. pica (Wileman, 1910) comb. nov., P. trimacula (Matsumura, 1927) comb. nov., P. wangi (Owada, 1992) comb. nov., P. dejeani (Oberthür, 1893) comb. nov., P. lucia (Oberthür, 1923) comb. nov., P. glacialis glacialis (Moore, 1872) comb. nov., P. glacialis parthenie (Jordan, 1907b) comb. nov., P. glacialis angustifasciata (Hering, 1922) comb. nov., P. glacialis postfasciata (Holloway, 2011) comb. nov. A checklist of the species and genera mentioned in the present study is given. Adults and genitalia of the newly described taxa and related ones are illustrated.